(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2004)
The Global Boundary Stratotype Section and Point of the Toarcian-Aalenian Boundary (Lower-Middle Jurassic) in Fuentelsaz Section is the first GSSP defined in Spain. Among the requirements of the ICS for the choice of the best boundary level are accessibility to the type-section and free access for research, and guarantees from the respective authority concerning to the free access and the permanent protection of the site. In our point of view, the most suitable protection figure to safeguard the fulfilment of the ICS’s requirements according to the Spanish Conservation Policy and Legislation is the Natural Monument. This paper deals with the conservation management and classification of the Fuentelsaz area as a Natural Monument, being the Comunidad de Castilla-La Mancha Authorities the ones that have to take the necessary steps to protect the site.